2013
DOI: 10.1161/circep.113.000348
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Ventricular Tachycardia and Its Electrophysiological Substrate Early After Myocardial Infarction

Abstract: Background— Sudden arrhythmic death after myocardial infarction (MI) is most frequent in the first month. Early programmed ventricular stimulation (within 1 week) post-MI has been able to identify long-term ventricular tachycardia (VT) occurrence. We aimed to determine the timing of development and stabilization of VT circuits after MI and how the evolution of the underlying substrate differs with VT inducibility. Methods and Results— MIs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
1
14
0
2
Order By: Relevance
“…In an ovine model, these re-entrant circuits of VT have been seen to form and stabilize within the first week after infarction. 45 Hsieh et al 45 demonstrated that inducibility of VT day 8 after infarction was concordant with inducibility of VT at day 100 in 100% of sheep. In this study, the earliest activation sites of the VTs, the cycle length, and the relationship to areas of myocardial injury were similar between the day 8 and chronic periods.…”
Section: Substrate For Re-entrant Tachycardiamentioning
confidence: 99%
See 2 more Smart Citations
“…In an ovine model, these re-entrant circuits of VT have been seen to form and stabilize within the first week after infarction. 45 Hsieh et al 45 demonstrated that inducibility of VT day 8 after infarction was concordant with inducibility of VT at day 100 in 100% of sheep. In this study, the earliest activation sites of the VTs, the cycle length, and the relationship to areas of myocardial injury were similar between the day 8 and chronic periods.…”
Section: Substrate For Re-entrant Tachycardiamentioning
confidence: 99%
“…V ovčím modelu byly pozorovány vznik a stabilizace těchto reentry okruhů KT v prvním týdnu po infarktu. 45 Hsieh a spol. 45 prokázali, že indukovatelnost KT osmý den po infarktu se shodovala s indukovatelností KT ve stý den u 100 % ovcí.…”
Section: Substrát Reentry Tachykardiíunclassified
See 1 more Smart Citation
“…9 In addition, animal experiments revealed early formation of arrhythmogenic substrate after induced myocardial infarction and suggested better outcomes after immediate ablation. 10,11 We hypothesized that the arrhythmia substrate evolves in the time, partially driven by the VT itself. Therefore, we aimed to determine whether CA in earlier stages of ventricular remodeling may improve the outcomes, compared with VT ablation performed as a treatment of last resort in patients with advanced stage structural heart disease.…”
Section: Clinical Perspective On P 1151mentioning
confidence: 99%
“…4 Ovine studies conducted at our institution have suggested that post-MI substrate for ventricular tachycardia develops within the first week and remains stable into the chronic phase. 5 Our intention in using an early LVEF cutoff, with the knowledge that it would improve, was to assess a larger population during the early high-risk period but to restrict ICD implantation through the use of EPS.…”
mentioning
confidence: 99%